STRENGTH PREDICTION OF RSM IN BOLTED CONNECTION OF ALAN BATU WOOD - Shahidan, Anuar; Abdul Razak, Abdul Karim; Norazzlina, M.Sa'don; Gaddafi, Ismaili; Faisal Amsyar, Redzuan; Norsuzailina, Mohamed Sutan; Runi Sylvester, Pungga; Nur Liza, Rahim; Pierre, Quenneville (Taylor’s University, 2026)
This study investigates the structural performance of bolted connections in Alan Batu wood to support the development of a local wood database for strengthening wall-diaphragm connections of unreinforced masonry (URM) buildings in Malaysia. Alan Batu wood was selected due to its common use as roof rafters and floor joists in URM buildings. Ten groups, each with ten replicates, were tested to assess bolted connection strength. Brittle failure was observed, confirming row shear failure. Since the material properties of Alan Batu are similar to Meraka wood, this study combines data from both to recommend design parameters (i.e., dry density and calibration factor) for optimising bolted connection strength predictions using the Row Shear Model (RSM). Analysis of the combined data showed that the Malaysian timber code (MS544-5) significantly underestimates bolted connection strength, potentially leading to over-sizing steel bolts and using more fasteners than necessary. The MS544-5 predictions had an average effectiveness of 45% compared to the 5th percentile experimental values, while the RSM showed a much higher average effectiveness of 80%. The design parameters proposed in this study optimise RSM strength predictions for Meraka and Alan Batu woods, offering cost-effective solutions for retrofitting URM wall-diaphragm connections.